Situation Report: Romania, 27 April 1977 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Party Journal Praises New Book on Economic Theory Measures to Improve Product Quality Bottleneck in the Shipbuilding Industry Romanians Find Oil Agricultural Production Co-Operatives Pensions for Agricultural Workers Improved (II) The Romanian Baptist Union